2018
DOI: 10.7324/japs.2018.8115
|View full text |Cite
|
Sign up to set email alerts
|

Potential efficacy of Coenzyme Q10 against oxytetracycline-induced hepatorenal and reproductive toxicity in male rats

Abstract: This study was performed to assess potential efficacy of Coenzyme Q10 (CoQ10) to restore oxytetracycline (OXT)-induced toxicity. Rats were distributed into four equal groups (6 each). The Control group received propylene glycol (0.5 ml p.o). CoQ10 group received Coenzyme Q10 (10 mg/kg BW p.o). OXT group (rats were injected intraperitoneally with 200 mg/kg BW oxytetracycline hydrochloride). OXT+CoQ10 group (rats were given the combined treatments). Treatments were used daily for seven days. Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Treatment of rats with CoQ10 revealed a significant increase in serum testosterone and testis index value when compared with the DOX group. Oda et al stated that supplementation of CoQ10 to oxytetracyclinetreated rats showed elevated serum levels of testosterone and restored relative testis weight [25]. Furthermore, CoQ10 as an antioxidant suppressed lipid peroxidation in testis.…”
Section: The Central Vein (C) At the Center Of Classic Hepatic Lobule And Cords Of Hepatocytes With Large Rounded Vesicular Nuclei (Arrowmentioning
confidence: 99%
“…Treatment of rats with CoQ10 revealed a significant increase in serum testosterone and testis index value when compared with the DOX group. Oda et al stated that supplementation of CoQ10 to oxytetracyclinetreated rats showed elevated serum levels of testosterone and restored relative testis weight [25]. Furthermore, CoQ10 as an antioxidant suppressed lipid peroxidation in testis.…”
Section: The Central Vein (C) At the Center Of Classic Hepatic Lobule And Cords Of Hepatocytes With Large Rounded Vesicular Nuclei (Arrowmentioning
confidence: 99%